2016
DOI: 10.3847/0004-637x/833/1/18
|View full text |Cite
|
Sign up to set email alerts
|

ON THE RELATIONSHIP OF UC H ii REGIONS AND CLASS II METHANOL MASERS. I. SOURCE CATALOGS

Abstract: We conducted VLA C-configuration observations to measure positions and luminosities of Galactic Class II 6.7 GHz methanol masers and their associated ultra-compact H II regions. The spectral resolution was 3.90625 kHz and the continuum sensitivity reached 45 µJy beam −1 . We mapped 372 methanol masers with peak flux densities of more than 2 Jy selected from the literature, 367 of them were detected. Absolute positions have nominal uncertainties of 0.3 . In this first paper on the data analysis, we present thre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(144 citation statements)
references
References 46 publications
9
133
1
1
Order By: Relevance
“…Weak water masers were detected by Titmarsh et al (2016) where S 22 GHz ∼ 0.7 Jy at v LSR = −21.6 km s −1 . Hu et al (2016) mapped the 6.668 GHz methanol masers of the high mass young stellar object (HMYSO) in 2012; it was only 5 Jy and had the same velocity extent as originally reported. The masers were also mapped by Rickert et al (2019) on 2015 September 09, who identified three 6.668 GHz methanol maser features at v LSR = −18, −17, and −16 km s −1 (F 6.668 = 1 − 3 Jy) in a single position.…”
mentioning
confidence: 71%
“…Weak water masers were detected by Titmarsh et al (2016) where S 22 GHz ∼ 0.7 Jy at v LSR = −21.6 km s −1 . Hu et al (2016) mapped the 6.668 GHz methanol masers of the high mass young stellar object (HMYSO) in 2012; it was only 5 Jy and had the same velocity extent as originally reported. The masers were also mapped by Rickert et al (2019) on 2015 September 09, who identified three 6.668 GHz methanol maser features at v LSR = −18, −17, and −16 km s −1 (F 6.668 = 1 − 3 Jy) in a single position.…”
mentioning
confidence: 71%
“…The light curve of the velocity-integrated flux density is presented in Figure 2 where the new and archival observations are complemented with the discovery detection (Szymczak et al 2000) and a single VLA observation (Hu et al 2016). The emission peaked around MJD 55296 and 56340 and the second outburst has a FHWM of ∼256 d and the rising phase a factor of two shorter than the declining phase.…”
Section: Resultsmentioning
confidence: 99%
“…The black squares and magenta circles denote the archival Torun 32 m data and fromSzymczak et al (2018), respectively. The blue triangle refers to the first detection(Szymczak et al 2000) and the black star marks the VLA observation at MJD 55990(Hu et al 2016).…”
mentioning
confidence: 99%
“…Due to such regions' compactness, their radio emission is very weak. However, an increasing number of such objects is now being detected with the JVLA (Rosero et al 2016;Hu et al 2016). van der Walt (2005) estimated the lifetime of class II methanol masers between 2.5 × 10 4 and 4.5 × 10 4 yr (depending on the assumed IMF).…”
Section: Discovery Of Three New Hot Cores In Sgr B2(n)mentioning
confidence: 99%